2013
DOI: 10.4068/cmj.2013.49.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Histopathological Comparison between Commercialized and Newly Designed Coronary Bare Metal Stents in a Porcine Coronary Restenosis Model

Abstract: The aim of this study was to compare the stent designed by Chonnam National University Hospital (designated as CNUH) with commercial cobalt-chromium coronary stent in a porcine coronary overstretch restenosis model. CNUH stent was subjected to mechanical performance tests. Pigs were randomized into two groups in which the coronary arteries (10 pigs, 10 coronaries in each group) had either CNUH stent or control commercial bare metal stent. Histopathologic analysis was assessed at 28 days after stenting. In mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…4b). Previously, we have been reported the superiority of CNUH stent (0.46 ± 0.079 N) on flexibility [21,22]. It was speculated that the mechanical properties of PCS is similar to CNUH since the peptide was coated to CNUH stent.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…4b). Previously, we have been reported the superiority of CNUH stent (0.46 ± 0.079 N) on flexibility [21,22]. It was speculated that the mechanical properties of PCS is similar to CNUH since the peptide was coated to CNUH stent.…”
Section: Discussionmentioning
confidence: 94%
“…Previously, we have reported that the own designed bare metal stent (BMS, designated as CNUH stent) [21,22] . It showed the great performance on flexibility, biocompatibility and moderate performance under the guide line of FDA in foreshortening and recoil performance.…”
Section: Preparation Of Bare Metal Stentmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMS (CNUH stent) used in the study was fabricated by laser-cut processing in a cobalt chromium alloy tube (L605 Co-Cr alloy) and electropolished to a strut thickness of \70 lm [14,15]. An ultrasonic spray method was used to apply coatings to the prepared BMS (3 9 16 mm).…”
Section: Preparation Of Aes Ses and Sasmentioning
confidence: 99%
“…In a previous study, our novel Co-Cr alloy BMS (CNUH stent) showed non-inferior histopathological effects compared to a commercial BMS. 9 PLA was purchased from EVONIK (UK) and sirolimus was purchased LC Laboratories (USA). An ultrasonic spray method was used to apply the coatings to the prepared BMS (3 × 16 mm).…”
Section: Preparation Of Pla-based Sirolimus Coating On a Novel Bare-mmentioning
confidence: 99%